Case of Stroke from Cerebral Vasculitis following Carfilzomib, Lenalidomide, and Dexamethasone Therapy in a Patient with Relapsing Multiple Myeloma - Deborah Osafehinti; Kaveh Zivari (Case Reports in Hematology)
Lenalidomide, a synthetic derivation of thalidomide, in recent years, has been the backbone of multiple myeloma treatment leading to improved survival. Common adverse effects from lenalidomide-based regimens include hypertension, heart disease, and venous thromboembolism. Hence, thromboprophylaxis is recommended to reduce the risk of stroke. We report a case of stroke from cerebral vasculitis in a patient receiving carfilzomib, lenalidomide, and dexamethasone for relapsing multiple myeloma, not previously published. Medical oncologists should be aware of other causes of stroke among multiple myeloma patients receiving a lenalidomide-based regimen to prevent its occurrence.